2017
DOI: 10.31234/osf.io/e4xw3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Liberal and Conservative Experience Across Academic Disciplines: An Extension of Inbar and Lammers

Abstract: Inbar and Lammers asked members of APA Division 8 (personality and social psychology) about their political orientation, hostility experienced related to their political orientation, and their willingness to discriminate against others based on perceived political orientation. In this replication and extension, 618 faculty members from various academic disciplines across four California State University campuses completed an online questionnaire that added parallel questions about the liberal experience to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
0
11
2
Order By: Relevance
“…Moreover, in the fields of sociology and behavioural science, several examples of significant contribution to the body of knowledge have been found with response rates far smaller than this one (e.g. 24% in Lam (2010), 26.4% in Honeycutt and Freberg (2017) and 37% in Tichenor et al (2017)).…”
Section: Implications Of Non-response On Results' Generalizationmentioning
confidence: 99%
“…Moreover, in the fields of sociology and behavioural science, several examples of significant contribution to the body of knowledge have been found with response rates far smaller than this one (e.g. 24% in Lam (2010), 26.4% in Honeycutt and Freberg (2017) and 37% in Tichenor et al (2017)).…”
Section: Implications Of Non-response On Results' Generalizationmentioning
confidence: 99%
“…Recent commentaries and research have explored political bias in the field of psychology (Haidt 2011). Specifically, this work has revealed a strong liberal bias not only in psychology but in science in general (Honeycutt and Freberg 2017). This implicit bias is blatant when taking a bird's eye view at research examining variations in political ideologies.…”
Section: Political Bias In Sciencementioning
confidence: 87%
“…While we will not provide a detailed discussion here, as such can be found elsewhere (Duarte et al 2015), suffice it to say that a cursory glance at research examining variation in political ideologies may give the impression that the field of psychology views those with conservative ideologies negatively. Sadly, work suggests that psychologists with conservative ideologies feel as if their field views them negatively (Honeycutt and Freberg 2017;Inbar and Lammers 2012). Therefore, this suggests we must redouble our efforts to address our research questions with objectivity, putting our personal biases, political or otherwise, aside.…”
Section: Political Bias In Sciencementioning
confidence: 99%
“…Similar results have been found in academic settings, suggesting that researchers themselves may not be immune to prejudicial behaviors against those on the other side of the political spectrum. For instance, surveys of academics in a variety of disciplines found that they report a desire to hire colleagues and support work done by individuals that share the same political views, and are more likely to discriminate against colleagues and candidates that are known to endorse other political values (Honeycutt & Freberg, ; Inbar & Lammers, ). Importantly, many of the studies exploring the discrimination liberals and conservatives enact upon one another find that the underlying mechanism guiding and legitimizing such behavior is the other side's value violations (Brandt et al., ; Chambers et al., ; Crawford et al., ; Crawford, ; Wetherell et al., ).…”
Section: Moral Polarizationmentioning
confidence: 99%